2009
DOI: 10.1111/j.1447-0349.2009.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver experience in mental illness: A perspective from a rural community in South Africa

Abstract: After the democratization of South Africa in 1994, the health-care system was reorganized in accordance with the primary health-care philosophy advocated by the World Health Organization. This was accompanied by a process of deinstitutionalization of mental health-care services, which has led families to become the main providers of care to individuals with mental illness. This study explores the experiences of informal family caregivers of persons with mental illness in a rural area in South Africa. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 40 publications
(73 reference statements)
8
55
0
Order By: Relevance
“…In France, psychiatric illness has been found to have detrimental effects on employment and overall quality of life of members of the affected person’s household 18 . Similar qualitative observations have been made in Botswana, 19 Nigeria 20 and South Africa 21 …”
Section: Introductionsupporting
confidence: 57%
“…In France, psychiatric illness has been found to have detrimental effects on employment and overall quality of life of members of the affected person’s household 18 . Similar qualitative observations have been made in Botswana, 19 Nigeria 20 and South Africa 21 …”
Section: Introductionsupporting
confidence: 57%
“…In rural areas of the United States where there are few resources, family members' perception of family burden due to mental health problems were found to be more negative than in urban areas where there are more treatment options and greater support (Kohn‐Wood & Wilson, ). Similar results were found among resource deprived countries such as South Africa (Mavundla, Toth, & Mphelane, ) and Botswana (Seloilwe, ). In both countries, researchers found that participants emphasized the negative impact of the emotional, social, and physical demands of living with and caring for a family member with a mental illness and the feeling that one's own physical and mental health was at risk.…”
Section: Scope Of the Problemsupporting
confidence: 77%
“…This dissatisfaction in health is influenced by the inadequate time the caregiver spends on their health concerns since most of their time is invested in their role. As caregivers adjust their social lives to the needs of patients diagnosed with mental illness, they usually have concerns about their own health but neglect them therefore their health deteriorates which eventually impacts on their perception of their overall QoL [18]. …”
Section: Discussionmentioning
confidence: 99%